Anxious and non-anxious adolescents' experiences of non-clinical magnetic resonance imaging research. - Haddad, A; Platt, B; James, A; Lau, J (2013)
Magnetic resonance imaging (MRI) has become a ubiquitous research tool for developmental neuroscientists interested in brain structure and function in children and adolescents. However, ethical concerns are sometimes raised about using MRI with children and adolescents, especially when participants have anxiety. We asked 17 clinically/sub-clinically anxious and 19 non-anxious adolescents about their experiences of taking part in MRI for research purposes. Although the anxious group reported experiencing more anxiety during the scan, these differences had attenuated by the time participants got home. We found no evidence that anxious adolescents would be less likely to choose to have another scan or would feel more nervous during another scan. There was some evidence that more trait anxious adolescents found the MRI study enjoyable. These findings should give ethics committees, clinicians, and parents confidence that so long as researchers exercise appropriate care, MRI research is acceptable to adolescents, including those with clinical anxiety.